Influence of the thermophysical properties of pavement materials on the evolution of temperature depth profiles in different climatic regions - Hall, Matthew R.; Dehdezi, Pejman Keikhaei; Dawson, Andrew R.; Grenfell, James; Isola, Riccardo (American Society of Civil Engineers, 2012)
The paper summarizes the relative influence of different pavement thermo-physical properties on the thermal response of pavement cross-sections, and how their relative behaviour changes in different climatic regions. A simplified one-dimensional heat flow modelling tool was developed to achieve this using a finite difference solution method for studying the dynamic temperature profile within pavement constructions. This approach allows for a wide variety and daily varying climatic conditions to be applied, where limited or historic thermo-physical material properties are available, and permits the thermal behaviour of the pavement layers to be accurately modelled and modified. The model was used with available thermal pavement materials properties and with properties determined specifically for the study reported here. The pavement materials included in the study comprised both conventional bituminous and cementicious mixes as well as unconventional mixtures that allowed a wide range of densities, thermal conductivities, specific heat capacities and thermal diffusivities to be investigated. Initially, the model was validated against in-situ pavement data collected in the USA in five widely differing climatic regions. It was found to give results at least as good as others available from more computationally expensive approaches such as 2D and 3D FE commercial packages. Then the model was used to compute the response for the same locations had the thermal properties been changed by using some of the unconventional pavement materials been used. This revealed that reduction of temperature range by several degrees was easily possible (with implications for reduction of rutting, fatigue and the Urban Heat Island effect) and that depth of penetration of peak temperatures was also achievable (with implications for winter freeze-thaw). However, the results showed that there was little opportunity to displace the peak temperatures in time.